Reversine: A Synthetic Purine with a Dual Activity as a Cell Dedifferentiating Agent and a Selective Anticancer Drug - Piccoli, Marco; Ghiroldi, Andrea; Monasky, Michelle M.; Cirillo, Federica; Ciconte, Giuseppe; Pappone, Carlo; Anastasia, Luigi (Current Medicinal Chemistry, 2020)
The development of new therapeutic applications for adult and embryonic stem cells has dominated regenerative medicine and tissue engineering for several decades. However, since 2006, induced Pluripotent Stem Cells (iPSCs) have taken center stage in the field, as they promised to overcome several limitations of the other stem cell types. Nonetheless, other promising approaches for adult cell reprogramming have been attempted over the years, even before the generation of iPSCs. In particular, two years before the discovery of iPSCs, the possibility of synthesizing libraries of large organic compounds, as well as the development of high-throughput screenings to quickly test their biological activity, enabled the identification of a 2,6-disubstituted purine, named reversine, which was shown to be able to reprogram adult cells to a progenitor-like state. Since its discovery, the effect of reversine has been confirmed on different cell types, and several studies on its mechanism of action have revealed its central role in inhibitory activity on several kinases implicated in cell cycle regulation and cytokinesis. These key features, together with its chemical nature, suggested a possible use of the molecule as an anti-cancer drug. Remarkably, reversine exhibited potent cytotoxic activity against several tumor cell lines in vitro and a significant effect in decreasing tumor progression and metastatization in vivo. Thus, 15 years since its discovery, this review aims at critically summarizing the current knowledge to clarify the dual role of reversine as a dedifferentiating agent and anti-cancer drug.
Keywords: reprogramming